Tris-hydroxymethylaminomethane (THAM): a novel organocatalyst for a environmentally benign synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles - Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2015)
simple, efficient and environmentally benign protocol has been developed for the one-pot, multicomponent synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles using a commercially available, inexpensive, non-toxic, and biodegradable tris-hydroxymethylaminomethane (THAM) as a novel organocatalyst. Ambient reaction conditions, wide scope, avoidance of conventional isolation as well as purification techniques and the reusability of the catalyst for five consecutive runs have improved the practical utility of this multicomponent reaction protocol manifold.

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane